PENGARUH PROMOSI, LOKASI DAN PERSEPSI HARGA TERHADAP KEPUTUSAN BERKUNJUNG DI TELAGA SARANGAN MAGETAN - Nurayudewi Lestari; Bonifasius Nainggolan (LPPM Universitas Asa Indonesia, 2022)
This study aims to analyze the effect of promotion, location and price perception on visiting decisions. Testing the research hypothesis using multiple linier regresion analysis andthe help of spss26. The survey was carried out by distributing questionnaires to 120 tourists who visited sarangan lake, magetan regency. The selection of respondents was done by accidental sampling technique because by chance meeting with the researcher can be used as a sample. The results show that an increase in the number of tourists requires promotion, location and price perception simultaneously. The results of the study also show that promotion, location and price perception play a significant role in increasing visiting decisions. This study has implications for increasing understanding regarding the relationship between promotion, location and price perception with the decision to visit telaga sarangan, magetan regency. The importance of the influence of location so that it can play a significant role in increasing visiting decisions.